Implementation of digital tool my english lab to improve oral skill of sixth grade students at Rubira school - Villón Chancay, Marlene Del Rosario (2024)
The following research focuses on improving the oral skills of sixth-grade students using interactive activities through digital tool "My English Lab." The study was conducted at the Rubira Educational Unit in Ecuador. The methodology used was quantitative methods to understand the effectiveness of My English Lab in each class during the teaching-learning process in which compared students using the tool with those receiving traditional instruction. The results emerged from the application of students who used My English Lab, where oral fluency, accuracy, pronunciation, comprehension, and memorization improved significantly compared to students who received traditional instruction. In conclusion, the safe and supportive environment provided by My English Lab allows students to feel comfortable practicing their oral skills, as this tool offers a variety of activities and exercises that allow students to practice their oral skills in different contexts. This demonstrated the potential of digital tools to revolutionize language learning, particularly for speaking, a traditionally challenging area